Determinants of tuberculosis trends in six Indigenous populations of the USA, Canada, and Greenland from 1960 to 2014: a population-based study. (March 2018) - Dehghani, Kianoush; Lan, Zhiyi; Li, Peizhi; Michelsen, Sascha Wilk; Waites, Sean; Benedetti, Andrea; Lejeune, Pierre; Torrie, Jill; Robinson, Elizabeth; Vejvoda, Berenica; Mullah, Muhammad; Redwood, Diana; et al.
Summary: Background: Tuberculosis continues to disproportionately affect many Indigenous populations in the USA, Canada, and Greenland. We aimed to investigate whether population-based tuberculosis-specific interventions or changes in general health and socioeconomic indicators, or a combination of these factors, were associated with changes in tuberculosis incidence in these Indigenous populations. Methods: For this population-based study we examined annual tuberculosis notification rates between 1960 and 2014 in six Indigenous populations of the USA, Canada, and Greenland (Inuit [Greenland], American Indian and Alaska Native [Alaska, USA], First Nations [Alberta, Canada], Cree of Eeyou Istchee [Quebec, Canada], Inuit of Nunavik [Quebec, Canada], and Inuit of Nunavut [Canada]), as well as the general population of Canada. We used mixed-model linear regression to estimate the association of these rates with population-wide interventions of bacillus Calmette-Guérin (BCG) vaccination of infants, radiographic screening, or testing and treatment for latent tuberculosis infection (LTBI), and with other health and socioeconomic indicators including life expectancy, infant mortality, diabetes, obesity, smoking, alcohol use, crowded housing, employment, education, and health expenditures. Findings: Tuberculosis notification rates declined rapidly in all six Indigenous populations between 1960 and 1980, with continued decline in Indigenous populations in Alberta, Alaska, and Eeyou Istchee thereafter but recrudescence in Inuit populations of Nunavut, Nunavik, and Greenland. Annual percentage reductions in tuberculosis incidence were significantly associated with two tuberculosis control interventions, relative to no intervention, and after adjustment for infant mortality and smoking: BCG vaccination (–11%, 95% CI −6 to −17) and LTBI screening and treatment (–10%, −3 to −18). Adjusted associations were not significant for chest radiographic screening (–1%, 95% CI −7 to 5). Declining tuberculosis notification rates were significantly associated with increased life expectancy (–37·8 [95% CI −41·7 to −33·9] fewer cases per 100 000 for each 1-year increase) and decreased infant mortality (–9·0 [–9·5 to −8·6] fewer cases per 100 000 for each death averted per 1000 livebirths) in all six Indigenous populations, but no significant associations were observed for other health and socioeconomic indicators examined. Interpretation: Population-based BCG vaccination of infants and LTBI screening and treatment were associated with significant decreases in tuberculosis notification rates in these Indigenous populations. These interventions should be reinforced in populations still affected by tuberculosis, while also addressing the persistent health and socioeconomic disparities. Funding: Public Health Department of the Cree Board of Health and Social Services of James Bay.